SINHAS-1 Maize Seed Production Through Male-Female Ratio and Pruning Technique - Ifayanti Ridwan; Muh Farid Bdr; yunus Musa; Hatta Jamil; A. Rusdayani Amin; Muhammad Fuad Anshori; Sakka Pati; N. Nursini; Annastya Nur Fadhilah (Agrotech Journal, 2020)
The research was aimed to obtain male and female rows ratio and best pruning technique towards SINHAS 1 maize production. This research was conducted in Experimental Farm Faculty of Agriculture, Hasanuddin University, Tamalanrea District, Makassar, South Sulawesi with elevation of 22,4 meters above the sea level throughout May – August 2020. The experiment was carried out in the form of Split Plot Design with male-female row ratio as main plot, which consisted of three levels: 1:2 ratio, 1:3 ratio, and 1:4 ratio. Sub plot was pruning techniques: no pruning, male parent pruning and leaf pruning under the cob of female parent. The result showed that the favorable male-female row ratio towards SINHAS 1 maize production was 1:4 ratio. Male parent pruning was the best pruning technique for SINHAS 1 maize production. The interaction between male-female ratio and best pruning technique was 1:3 male-female ratio with male parent pruning technique. Characters that showed positively direct significance towards productivity were cob diameter, cob length, and number of seed rows per cob